Design and development of an integrated grating and slicing machine for starchy vegetables - Lok, Chung Yee (2012)
Conventional processes of grating and slicing that produce both grated and sliced products normally involved two units of independently operated machines. In this study, grating and slicing processes have been combined into a single operation through an integrated machine for simultaneous operations. The purpose of integrating both processes is to reduce operation cost, time, energy consumption, and the number of unit operations involved in the processing system, both grating and slicing production. Three objectives were outlined to achieve in this research. The first objective was to determine the selected physical properties of starchy vegetables (white potato, sweet potato, tapioca, and yam) to be applied to the new machine. The second objective was to develop and design an integrated grating and slicing machine for simultaneous operation. The final objective was to evaluate the performance of an integrated machine for production of grating and slicing starchy vegetables. Two selected physical properties of starchy vegetables that were studied are hardness and moisture content. These properties were measured using a destructive testing method of texture and moisture analyzer. The information on the properties of starchy vegetables hardness and moisture content are important to be determined prior to design the food processing equipments which relates to the grating and slicing processes. The selected starchy vegetables used for this study were white potato, sweet potato, tapioca and yam. It was found that the maximum hardness of white potato, yam, sweet potato and tapioca were 65.43 N, 117.82 N, 166.57 N and 196.98 N respectively. The range of moisture content of these vegetables is 60 to 78%. Based on the hardness results, it was determined that the minimum requirement for the cutting force of the integrated machine must not be less than 700 N/m. During the design and development phase, the machine‟s design specifications were identified to ensure that the simultaneous grating and slicing operations in an integrated machine are capable to process the raw materials. The design methodology was first begun with product development process, conceptual design, design selection, detail design, prototype development and finally, machine and production assessment. This machine is developed to overcome the problems faced in conventional grating and slicing processes using two units of independent operation machines. The present state of this machine is suitable for use in industrial processing level, leading to greater improvement in reducing energy and operating consumption (lower power at 750 W with variable speed at 0 – 180 rpm) with lower speed for grated production range at 750 – 1200 kg/hr and sliced production range at 250 – 400 kg/hr. This newly designed machine is easy to setup, handle, store, clean,service, and maintain as well as capable to produce quality grated (10 x 10 mm at 750 to 1200 kg/hr) and sliced (2 mm thick at 250 – 400 kg/hr) products. This study has demonstrated that the newly integrated machine is ready to be used for the production of food chips and finger products.